Assessing the Magnetic Shielding Effectiveness of Low Carbon Steel, Permalloy, and Mu-metal on Small Satellite Reaction Wheel Assemblies using Finite Element Analysis - Susilo, Hogan Eighfansyah; Budiantoro, Poki Agung; Fitrianingsih, Ery; Mayditia, Hasan; Nasser, Eriko Nasemudin; Farmasiantoro, Adi; Fauzi, Ahmad; Slamet, Widodo; Tahir, Andi Mukhtar; Pratiwi, Nindhita (Journal of Multidisciplinary Applied Natural Science, 2026)
Magnetic cleanliness is essential for small satellites carrying sensitive payloads such as magnetometers and particle detectors. Reaction wheel assemblies (RWAs) represent a primary source of stray magnetic fields, requiring effective shielding under strict mass and volume constraints. This study uses three-dimensional finite element analysis (FEM) in ANSYS Maxwell to evaluate the shielding effectiveness (SE) of high-permeability alloys (Mu-metal and Permalloy 80) and low-carbon steels (AISI 1008/1010) at thicknesses of 1–3 mm, with aluminum 6061-T6 as a non-magnetic baseline, within a cylindrical RWA enclosure geometry. Results reveal a critical design trade-off: High-permeability alloys provide superior attenuation (>65 dB at 100 mm; residual field <150 nT) and high mass efficiency (>700 dB/kg) but saturate at low flux density (0.8 T) and are costly. Low-carbon steels offer moderate SE (34–40 dB) with far higher saturation tolerance (2.2 T), structural robustness, and lower cost. Thickness scaling shows diminishing returns beyond 2 mm for high-permeability materials, whereas steels improve more linearly. Rather than proposing a new shielding concept, this study applies an integrated FEM-based evaluation approach for small satellite platforms to consistently assess shielding effectiveness, nonlinear saturation behavior, thickness scaling, and mass efficiency of candidate materials within a reaction-wheel-representative geometry under identical boundary conditions.